Brief: the economics of water for transitioning food systems - Dankens, S.; Buisson, Marie-Charlotte (International Water Management Institute, 2025)
The global water cycle is the lifeblood of our planet and underpins all economic activities, from medical goods and services to food production and energy generation. It includes blue water, the water in lakes, rivers, and aquifers that is readily extractable by humans, and green water, the moisture held in soil and plants that evaporates or transpires into the air. Green water produces over half of the rainfall over land and is therefore a key source of freshwater, also known as blue water.